Information Systems Architecture and Technology: Proceedings of 37th International Conference on Information Systems Architecture and Technology - ISAT 2016 - Part III - Świątek, Jerzy; Wilimowska, Zofia; Borzemski, Leszek; Grzech, Adam (Advances in Intelligent Systems and Computing,, 2017)
This four volume set of books constitutes the proceedings of the 2016 37th International Conference Information Systems Architecture and Technology (ISAT), or ISAT 2016 for short, held on September 18-20, 2016 in Karpacz, Poland. The conference was organized by the Department of Management Systems and the Department of Computer Science, Wrocław University of Science and Technology, Poland. The papers included in the proceedings have been subject to a thorough review process by highly qualified peer reviewers. The accepted papers have been grouped into four parts: Part I-addressing topics including, but not limited to, systems analysis and modeling, methods for managing complex planning environment and insights from Big Data research projects. Part II-discoursing about topics including, but not limited to, Web systems, computer networks, distributed computing, and mulit-agent systems and Internet of Things. Part III-discussing topics including, but not limitedto, mobile and Service Oriented Architecture systems, high performance computing, cloud computing, knowledge discovery, data mining and knowledge based management. Part IV-dealing with topics including, but not limited to, finance, logistics and market problems, and artificial intelligence methods.